Tingkat Pengetahuan Ibu Hamil Tentang Anemia Di Puskesmas Plumbon Kabupaten Indramayu - Nengsih Yulianingsih; Hasim Asyari; Sally Yustinawati Suryatna; Marsono Marsono; Lisda Hayati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Maternal Mortality Rate (MMR) is an indicator to see the level of women's health. Based on the Indonesian Health Demographic Survey (SDKI), MMR in Indonesia in Indonesia, the maternal mortality rate in Indonesia was 305/100,000 live births, with this, maternal mortality cases in Indonesia still have not succeeded in reaching the SDG's target,. Meanwhile in Indramayu Regency in 2023, namely 34 mothers out of 42,569 births, a decrease from the figure in 2022. Indramayu Regency has the highest prevalence of anemia, namely 32.29%. The aim of this research is to determine the level of knowledge of pregnant women about anemia at the Plumbon Regency Health Center Indramayu. The method used is descriptive research with a cross-sectional research design. Data was obtained using a questionnaire sheet from previous research which was then retested with a total of 35 mothers as respondents. The results showed that respondents had a good level of knowledge of 48.1%, 77.8% were aged 20-35 years, 81.5% had a high school/vocational school education, and 55.6% did not work. The conclusion is that the majority of mothers who have well-informed babies are aged 20-35 years, have a high school/vocational education, and do not work.